Transthoracic Needle Biopsy: How to Maximize Diagnostic Accuracy and Minimize Complications - Chaeuk Chung; Yoonjoo Kim; Dongil Park (Tuberculosis and Respiratory Diseases, 2020)
Although transthoracic needle biopsy (TTNB) was introduced for lung biopsy about 40 years ago, it is still mainstay of pathologic diagnosis in lung cancer, because it is relatively inexpensive and can obtain tissue regardless of the tumor-bronchus relationship. With several technological advances, proceduralists can perform TTNB more safely and accurately. Utilizing ultrasound-guided biopsy for peripheral lesions in contact with the pleura and rapid on-site evaluation during the procedure are expected to make up the weakness of TTNB. However, due to the inherent limitations of the percutaneous approach, the incidence of complications such as pneumothorax or bleeding is inevitably higher than that of other lung biopsy techniques. Thorough understating of each biopsy modality and additional technique are fundamental for maximizing diagnostic accuracy and minimizing the complications.